Women's Agency in Resolving Religious Conflict in Indonesia: A Gender-Based Literature Review - Haryani, Elma; Saputro, M. Endy (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
Religious social conflicts in Indonesia routinely expose women to multiple physical, economic and symbolic harms, yet policies and studies still frame them primarily as passive victims. This article asks how, why and to what extent women contribute to resolving these conflicts. This research is based on feminist conflict theory and the women, peace and security agenda, a literature review research type with qualitative methods following the PRISMA protocol. The results found three dominant conflict patterns emerged, namely sectarian, communal and identity-political. Women responded through four overlapping strategies: community mediation, interfaith dialogue, trauma healing circles and livelihood cooperatives, which collectively shortened hostilities by about a quarter and increased household income resilience by almost a third and only 18 percent of the policies reviewed explicitly supported these initiatives. The conclusion that the recognition of women as peace actors strengthens the sustainability of agreements and social recovery, and recommends the institutionalization of gender quotas, special funding and legal protection within the framework of religious moderation and RAN-P3AKS in Indonesia.